Photography as Absence: Implicit Histories (Africa, Late Nineteenth and Early Twentieth Centuries) - (:unkn) unknown (My University, 2023)
Photographic material can sometimes pose an overwhelming and distorting presence, especially when it comes to the writing of history. Some of the first visual recordings of African social worlds via photography would long serve as a model for images of the continent. This phenomenon has only been reinforced by recirculations of images from the late nineteenth and early twentieth centuries. Intended as a counterpoint, this article will contemplate a paradoxical history of photography by considering it based not on its presence but on its very absence. A work of history supported by photographic and written sources from the years 1870 to 1910, this contribution focuses on photography as absence, as disappearance, and as erasure. This implicit history focuses on various essential phenomena that characterize the (non)production of photographic images of African social worlds in the age of colonial expansion. It first deals with the key question of the material destruction of old photographs of Africa. For a variety of reasons, an entire part of what was photographed is now either lost or in the process of becoming lost. One of the long-standing major effects of this has been a double erasure of African photography pioneers, who are poorly represented or underrepresented in institutional archives and have been deprived of historiographical attention; in many cases, their history remains to be written. The article then raises the question of refusals to pose and potential refusals to take photographs. We will see several scattered traces of such evasions of photography. The problem of self-censorship and the very restricted circulation of certain images, particularly those threatening the stability of colonial narratives, will also be studied at this juncture. Finally, the article will take a closer look at the photographs taken by Alex J. Braham. This individual, a district agent in Ogugu (southern Nigeria) for the Royal Niger Company at the turn of the twe
Keywords: African Research